Ab Initio Molecular Dynamic Study of Structural and Electrical Properties of Gold Nanoparticle - Fuad, Abdullah Aufa; Zaidan, Andi Hamim; Supardi, Adri (Indonesian Applied Physics Letters, 2022)
The goal of this research is to know structural and electrical properties of gold nanoparticle (GNP) through ab initio molecular dynamic (AIMD) method. Structural properties are explained by the study of coordination number, bond angle distribution, and radial distribution function. Electrical properties are explained by the study of band structure and density of states. GNP samples used in this research are liquid, amorph, and icosahedral. The main software used for AIMD numerical calculation was SIESTA. Liquid GNP is dominated by coordination number of 9, amorf GNP 10, icosahedral GNP 18. Bond angle distribution of liquid GNP has 1 peak in 60o, amorph GNP has 4 peak in 60o, 90o, 120o, 175o, icosahedral GNP has complete all 6 peak. Internal spacing of liquid GNP is 2,7 í…, amorph is 2,8 í…, icosahedral is 1,9 í…. Study of band structure show that the width of liquid GNP bandgap is 0,040 eV, amorph is 0,071 eV, icosahedral is 0,200 eV. While the width of bandgap by density of state study for liquid GNP is 0,053 eV, amorph is 0,085 eV, icosahedral is 0,200 eV.